2023
DOI: 10.3390/healthcare11060834
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Race and Gender-Related Discrimination on the Psychological Distress Experienced by Junior Doctors in the UK: A Qualitative Secondary Data Analysis

Abstract: Almost half of NHS doctors are junior doctors, while high proportions are women and/or Black, Asian, and Minority Ethnic (BAME) individuals. Discrimination against this population is associated with poorer career-related outcomes and unequal representation. We aimed to qualitatively explore junior doctors’ experience of workplace racial and gender-based discrimination, and its impact on their psychological distress (PD). In this study, we carried out a secondary analysis of data from a UK-based parent study ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…On the other side, ethnic minority doctors also experience challenges in career progression, including systemic biases, workplace discrimination, and a lack of representation in leadership roles 5 . These disparities not only hinder the full potential of the healthcare system but also undermine the trust and confidence of both patients and doctors.…”
Section: Sushruta J Health Policymentioning
confidence: 99%
“…On the other side, ethnic minority doctors also experience challenges in career progression, including systemic biases, workplace discrimination, and a lack of representation in leadership roles 5 . These disparities not only hinder the full potential of the healthcare system but also undermine the trust and confidence of both patients and doctors.…”
Section: Sushruta J Health Policymentioning
confidence: 99%
“…Unfortunately, physicians commonly report gender discrimination, which significantly impacts the affected person’s performance and quality of life. In the United Kingdom, Hussain et al ( 35 ) qualitatively analyzed this phenomenon and found that affected individuals reported suffering from high levels of stress, fear, mistrust, low resilience, and retention. These microaggressions, harassment, or discrimination against women can be observed in regions with questionable medical professionalism, underestimating their potential and skills in practice.…”
Section: Risk Factors For Suicidal Ideation and Suicide In Physiciansmentioning
confidence: 99%